Diseño e implementación de una aplicación bajo dispositivos android y windows phone para la consulta de medicamentos a fin de evitar la automedicación en la población del municipio de lorica (2016)
In the present research is aimed at creating a mobile application on mobile Android and Windows Phone that allows people to consult drugs differently according to their contraindications or encumbrances alerting the user through alerts, plus usurious you can obtain information from appropriate use of prescription and non-prescription, you can view information about IPS and EPS dare Google Maps, enter the page INVIMA "national institute surveillance of medicines and food in Colombia", perform opinions directly, qualify the application to disclose whether degree of acceptance of the application. The process of developing and implementing the application was made using mobile apps with HTML, CSS, JS, JavaScript, material design and PhoneGap Build compiled; with its own web server. In order to avoid self-medication.